Communication and Retoric of Dakwah Style of T.G.K.H. Muhammad Zainul Majdi at the 70—80th NWDI Birthday Preaching in Pancor - Muh Irfan; Jusratul Aini (ppjbsip, 2019)
This study aims to describe the style and language of TGB communication in public studies of the 77th, 79th, and 80th NWDI rituals. This type of research uses qualitative descriptive method. Qualitative research method is a research method used to examine the condition of natural objects, where researchers are as a key instrument, data collection techniques are done in triangulation, data analysis is inductive, and qualitative research results emphasize the meaning of generalization. The data and data sources in this research are 77,797 and 80 public lecture videos of NWDI, downloaded from youtube. The problem discussed in this research is how communication style and rhetoric of TGB da'wah in public study of 77th, 79th, and 80th NWDI rituals. TGB communication style is a combination of low context communication style and positive side of high context communication characterized by the delivery style firm, straightforward, clear, peaceful, cool, calm, and able to play the rhythm when lecturing. The form of TGB's rhetoric of da'wah is a merging of aspects of rhetoric with forms of rhetoric. Aspects of rhetoric are diction, code transfer, code mixing, and politeness. The forms of TGB rhetoric are seen from the style of languages and non-languages. Both are very influential in the rhetoric of TGB preaching. The rhetorical perspectives are due to the application of the language style has been adjusted to the condition of pilgrims and place of application.